Land size and efficiency in agriculture: the case of Ethiopian smallholder farmers. A meta-analysis - Girma Asefa, Yohannes; Ayalew Muluken, Abera (Frontiers in Sustainable Food Systems, 2024)
Even if smallholders have large share in Ethiopian economy they operate under potential. Land use is the base in determining efficiency of farmers. However, the effect of land size on efficiency is still a controversial issue in the country. This review is designed to determine the effect of land size on farmers' efficiency. Random effect model showed that farmers with smaller land size (< 0.5ha) are by 21% more efficient than large land size holders. Moreover, the meta regression result showed that resource endowment, labor quality, information contact and total income are important moderators for the presence of heterogeneity for effect size among studies. It was deduced that farmers are efficient under smaller land size since they have resource to manage their farm appropriately. Therefore, Improving farmers' production skill, providing input subsidy and upgrading development agents' skill are crucial to boost farmers' efficiency in the country.